Seven deadly sins: "retrospectivity, culpability and responsibility". Issue 1 (2nd January 2016) - McCormick, Roger; Duarte, Tania; Stears, Chris
Abstract : Although banks' reputations are uniformly at a low ebb and the costs of misconduct remain high, are all forms of misconduct equally bad? This article suggests that distinctions can be made and that there are different grades of moral culpability (after all, no business is perfect). Seven categories are suggested. Conspiracy to defraud is in the "worst" category whilst it is suggested that (for example) a technical failure to understand the technical requirements of client money rules should attract lees opprobrium. The categories enable a "scoring system" for moral standards to be devised and an example of how this could work is shown in relation to the four main UK banks.